Treating acute anxiety in patients with COVID-19 - Khawam, Elias; Khouli, Hassan; Pozuelo, Leo (Cleveland Clinic Journal of Medicine, 2020)
At present, there are no firm guidelines for the treatment of COVID-19–related emotional distress. The current approach is based on our knowledge of how to manage anxiety in medically ill patients, taking into consideration all associated medical comorbidities, drug-drug interactions, and the patient’s specific needs and preexisting mental illness. Interventions should be implemented at the bedside to augment the patient’s own resiliency in coping with these stressful events. A targeted combination of psychopharmacology (targeting acute anxiety and panic symptoms) and psychotherapy (relaxation techniques, breathing exercises, and encouragement) is recommended.